The Impact of Learning Difficulties on Academic Achievement Students: Analysis of Causal Factors and Solutions - Nurlaili Hidayatul Baiti; Ayu Novtiana Devri; Kharisma Idola Arga (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
In the world of education, learning difficulties are a complex problem that can have a significant impact on student academic achievement. Analysis of causal factors and solutions is important in understanding these dynamics. Factors that cause learning difficulties include health conditions, learning environment, and individual characteristics of students. The impact of learning difficulties can be felt in declining grades, emotional disturbances, and limitations in developing students' potential. However, through the right approach, solutions can be found. Solutions such as learning differentiation, additional support programs, and partnerships with parents are key in helping students overcome learning difficulties and improve their academic performance. These steps provide opportunities for all students to reach their optimal learning potential. This research explores in depth the relationship between learning difficulties and academic achievement, and analyzes the underlying causal factors. Through a better understanding of these issues, educators, education professionals, and parents can work together to create learning environments that are inclusive, supportive, and facilitate students' holistic development. This will have a positive impact in improving student learning outcomes and preparing them for success in the future.